Perkin-Elmer Model 421 Grating Spectrophotometer - Perkin-Elmer Corporation (1960)
General view of an unidentified technician operating a Perkin-Elmer Corporation Model 421 Grating Spectrophotometer.
Keywords: Employees; Perkin-Elmer Corporation; Scientific apparatus and instruments; Spectrophotometer; Corporations; Spectrophotometry